The first ethanol sclerotherapy of an accessory cavitated uterine mass - Merviel, Philippe; Lelievre, Caroline; Cambier, Tatiana; Thomas‐Kergastel, Isabelle; Dupré, Pierre‐François (Clinical case reports, 2021)
Accessory cavitated uterine mass (ACUM) is a very rare, underdiagnosed pathology. It is treated with radical surgery, which results in uterine scarring. Here, we describe the first case of ethanol sclerotherapy of an ACUM, modeled on the treatment of recurring endometrioma. Ethanol sclerotherapy avoids uterine scarring and the secondary risk of uterine rupture and enables the rapid achievement of pregnancy. Accessory cavitated uterine mass (ACUM) is a very rare, underdiagnosed pathology. It is treated with radical surgery, which results in uterine scarring. Here, we describe the first case of ethanol sclerotherapy of an ACUM, modeled on the treatment of recurring endometrioma. Ethanol sclerotherapy avoids uterine scarring and the secondary risk of uterine rupture and enables the rapid achievement of pregnancy.